ACSL3 is an unfavorable prognostic marker in cholangiocarcinoma patients and confers ferroptosis resistance in cholangiocarcinoma cells - Apiwit Sae-Fung; Nawaporn Vinayavekhin; Bengt Fadeel; Siriporn Jitkaew (npj Precision Oncology)
Abstract Cholangiocarcinoma (CCA) is a bile duct malignancy. Our previous comprehensive analysis showed that ferroptosis-related genes can stratify CCA patients into low-risk and high-risk groups based on survival time. Here, we explored the role of ferroptosis in CCA by analyzing mRNA expression in CCA patients from public databases. We identified acyl-CoA synthetase long chain family member 3 (ACSL3) as a potential ferroptosis suppressor in high-risk CCA patients. Using a panel of CCA cell lines, we confirmed ACSL3 upregulation in CCA cell lines associated with high-risk CCA, correlating this with resistance to the ferroptosis inducer RSL3. Lipidomic analysis revealed increased monounsaturated fatty acid (MUFA)-containing phospholipids in resistant cell lines. ACSL3 silencing sensitized these cells to RSL3. Resistance to ferroptosis was also dependent on exogenous MUFAs and was enhanced by lipid droplet biogenesis inhibition. These findings highlight ACSL3 as a promising target for therapeutic strategies aimed at overcoming ferroptosis resistance in CCA.